Detailed dynamic mechanical analysis of thermomechanically stable melt‐processed PEK–MWCNT nanocomposites. Issue 7 (15th November 2016) - Chauhan, Sampat Singh; Singh, Bhanu P.; Malik, Rajender Singh; Verma, Pawan; Choudhary, Veena
Abstract : This article reports the detailed study of dynamic mechanical properties of multiwalled carbon nanotubes/poly(ether ketone) nanocomposites prepared by melt blending. The dynamic mechanical characterisitic parameters such as storage modulus ( E ′), loss modulus ( E ″) and damping factor (tan δ ) were explored in detail to investigate the adhesion factor ( A ), strength factor ( B ), efficiency factor ( C ), and entanglement density ( N ). Adhesion factor, which is inversely related to the degree of interaction between nanotubes and matrix, decreased with increase in MWCNT loading. Strength factor ( B ) which is a direct measure of interaction between MWCNTs and PEK increased with increase in MWCNT loading. The effect of nanotubes on moduli of composites is calculated in terms of coefficient of reinforcement ( C factor). Lower is the value of coefficient ( C ) higher will be the effectiveness of reinforcement on moduli of composites. It decreased from value of 1 at 1 wt% MWCNTs loading in PEK to 0.67 at 5 wt% MWCNTs loading which point towards increased effectiveness of MWCNTs at 5 wt% loading for excellent properties. To compliment these findings, entanglement density ( N ) was also calculated. Furthermore, Cole–Cole analysis was carried out to demonstrate the compatibility of both the components in composite system. POLYM. COMPOS., 39:2587–2596, 2018. © 2016 Society of Plastics Engineers